Investigations on reproductive and sexual health in Chilean indigenous populations and the lack of ethnic relevance - Dides Castillo, Claudia; Pérez Moscoso, María Soledad (Acta Bioethica, 2007)
This essay argues about the ethnic relevance of investigations carried out in Chile on sexual and reproductive health from 1990 to 2004, based on a national diagnosis on the subject. Most of these investigations did not consider the cultural and ethnic diversity of our country, so this is a pending issue. Furthermore, the tensions implied by the lack of ethnic relevance in investigations about sexual and reproductive health are also raised..